Dental anxiety and phobia among medical and dental undergraduates in Universiti Teknologi MARA (UiTM): a cross-sectional study / Izyan Hazwani Baharuddin ... [et al.] - Baharuddin, Izyan Hazwani; Zainal, Mukarramah; Asmaon, Aza Fazura; Ghazali, Izzul Alif; Mohd Kama, Muhammad Syukri; Razlan, Aimi Nadia (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objective: To assess the prevalence of dental anxiety and phobia among Malaysian medical and dental undergraduates of 2019. Materials and Methods: A validated Index of Dental Anxiety and Fear Scale (IDAF-4C+) questionnaires were distributed to medical and dental undergraduates in UiTM Sungai Buloh (n=460) via stratified random sampling. Demographic characteristics data were also collected. A cut point of 2.5 in average score for dental anxiety and fear (IDAF-4C) module was set to indicate the presence of dental anxiety. Descriptive statistics was used to determine the prevalence at while Pearson's correlation was used to check its correlation towards related dental stimuli. The association of sociodemographic factors towards dental anxiety and fear were evaluated by logistic regression. Results: This study found that medical undergraduates reported higher prevalence of dental fear (25.6%) as compared to dental undergraduates (18.9%). The highest stimuli correlated to dental anxiety and fear is 'feeling sick, queasy or disgusted' (r=0.537) followed by 'not being in control of what is happening' (r=0.484). Having unpleasant dental experience rose the likelihood of dental anxiety and fear by four times. Those from high-income family has 51.7% lower likelihood of dental anxiety and fear versus to those from low-income family. Conclusion: We conclude that dental anxiety is relatively prevalent even among medical and dental undergraduates in Malaysia. Feeling sick, queasy and disgusted are found to be the most correlated stimulus among medical undergraduates.